Competing audio-visual industries : a business history of the influence of SABC-TV on the Afrikaans cinematic film industry, c.1976-c.1986 - Coetzee, Coenraad Johannes (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.